Relações étnico-raciais na alfabetização científica: Contextos do livro didático de ciências no ensino fundamental - Silva, Brunna Alves da (2021)
The research is linked to the Graduate Program in Education of the Federal University of Uberlândia, corresponding to the Research Line Education in Sciences and Mathematics and aimed to present an in-depth discussion about ethnic-racial relations from the contextual and imagery context of the Teláris didactic collection referring to the Science curricular component. Constituting itself as a research problem, to analyze what are the contributions and limits of the Science textbook to work in an emancipatory perspective in favor of an anti-racist education. It is presented as a general objective the identification of possibilities in the science textbook and its real conditions to favor the deconstruction of the colonizing look of teachers and students through an anti-racist education and as specific objectives the characterization of the approach of content related to ethnic relations -racial in the Didactic Science Collection. In addition to studying possibilities of use with a view to building a critical view of ethnic-racial relations in scientific literacy. The theoretical foundation proposes the path of development of ethnic-racial relations in education. Starting from the definition point of this term, the conceptualization of the term race, the struggle of social movements, mainly the Black Movement for the guarantee of the right to education, the implementation of Law 10.639/03, and the possible challenges that still surround the legal framework. A bibliographic survey was carried out on the SciELO platform on the subject as a way of characterizing the scenario of productions related to the subject that provided us with subsidies to understand ethnic-racial relations in the field of education. Through this, it was possible to build categorizations that indicate important aspects in relation to the main points of approach of these researches, showing that there is a greater bibliographic production regarding the respective legal framework of Law 10.639/03, affirmative policies and teacher training, where the The theme of the textbook corresponded to the one with the lowest coverage in the studies. The methodological trajectory contextualizes and justifies the choice of Content Analysis in association with Depth Hermeneutics, passing through Critical Racial Theory, since, throughout the analysis, the complaints about contexts and images, propose a counter-narrative, which, in addition to the denunciation of structural racism, made it possible to advance in the interpretation of the data and to deepen the understanding of its main implications for scientific literacy.The characterization ends with a presentation of an individual evaluation of the four volumes and general characterization of the selected collection.